Polymer composite manufacturing using a pultrusion process: a review - Abd Manab, Mohd Fairuz; Salit, Mohd Sapuan; Zainudin, Edi Syams; Jaafar, Che Nor Aiza (Science Publications, 2014)
Pultrusion is the one of technologies to fabricate the polymer composites to be used in many industries such as in aerospace, automotive and construction industries. The high performance pultruded products that are produced by this technique offer high fibre content of at least 70%. In order to produce high quality pultruded profiles, there are variables such as fibre impregnation, resin viscosity, pulling speed and curing temperature that have to be considered and these variables are discussed in this study. The review on the recent research in pultrusion process, types of resins used in pultrusion process and mechanical properties of pultuded composites are presented.